2005
DOI: 10.1017/s0003598x00115017
|View full text |Cite
|
Sign up to set email alerts
|

Did the first farmers of central and eastern Europe produce dairy foods?

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(116 citation statements)
references
References 22 publications
5
106
0
5
Order By: Relevance
“…Already, lipid residue analysis has shown that some of the earliest ceramic vessels in Central and Northern Europe and Northwestern Anatolia were used for processing dairy products (18)(19)(20). Although these findings seemingly reinforce the link between pottery and farming, we note that the majority of Early Neolithic pots analyzed so far cannot be securely associated with either wild or domesticated products.…”
Section: Gc-combustion-isotope Ratio Msmentioning
confidence: 57%
“…Already, lipid residue analysis has shown that some of the earliest ceramic vessels in Central and Northern Europe and Northwestern Anatolia were used for processing dairy products (18)(19)(20). Although these findings seemingly reinforce the link between pottery and farming, we note that the majority of Early Neolithic pots analyzed so far cannot be securely associated with either wild or domesticated products.…”
Section: Gc-combustion-isotope Ratio Msmentioning
confidence: 57%
“…Today, the increase in cattle and the exploitation of secondary products is clearly seen during the Neolithic, where mixed husbandry regimes were practiced (Copley et al 2003;Craig et al 2003Craig et al , 2005Evershed et al 2008;Greenfield and Arnold 2015;Orton 2012;Spangenberg et al 2006). Instead, the early Copper Age faunal remains, although particularly limited, have begun to reveal variations in the proportion of domestic species at sites.…”
Section: Evidence Of Animal Husbandry Practicesmentioning
confidence: 99%
“…In Scandinavia, further to the north, dairy fat residue was found in Corded Ware culture at c. 2500 calBC (Cramp et al 2014b). Oliver Craig et al (2005) provided much earlier data for milk processing in the Early Neolithic in Southeast Europe. Degraded ruminant fatty acid in pottery in the Star≠evo-Cris (5950-5500 calBC) and Köros cultures (5800-5700 calBC) suggest milk products and milk processing, i.e.…”
Section: From Biomolecular To Stable Isotope Markers: From Meat To Milkmentioning
confidence: 99%